COVID-19 and Living space challenge. Well-being and Public Health recommendations for a healthy, safe, and sustainable housing. - D'Alessandro, Daniela; Gola, Marco; Appolloni, Letizia; Dettori, Marco; Fara, Gaetano Maria; Rebecchi, Andrea; Settimo, Gaetano; Capolongo, Stefano (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: The ongoing pandemic of COVID-19 is a strong reminder that the lockdown period has changed the way that people and communities live, work, and interact, and it’s necessary to make resilient the built environment, both outdoor and mainly the indoor spaces: housing, workplaces, public buildings, and entertainment facilities. How can we re-design the concept of Well-being and Public Health in relation to the living places of the future? Methods: According to the previous statements and scenario, this paper aims to integrate the building hygiene and well-being, focusing the possible responses, both existing and for the new buildings, taking home a strong message from this “period” of physical distancing. Results: The Well-being and Public Health recommendations for a healthy, safe, and sustainable housing are framed into the following key points: 1. Visible and accessible green elements and spaces; 2. Flexibility, adaptability, sharing, and crowding of living spaces, and compliant functions located into the buildings; 3. Re-appropriation of the basic principles and archetypes of sustainable architecture, thermal comfort and Indoor Air Quality (IAQ); 4. Water consumption and Wastewater Management; 5. Urban Solid Waste Management; 6. Housing automation and electromagnetic fields; 7. Indoor building and finishing materials. Conclusions: The Well-being and Public Health recommendations for a healthy, safe and sustainable housing may provide a useful basis for Designers, Policy Makers (fostering tax incentives for building renewal), Public Health experts and Local Health Agencies, in promoting actions and policies aimed to transform living places in healthier and Salutogenic spaces.